RELEVANSI NILAI-NILAI DAKWAH NABI MUHAMMAD DALAM MEMBANGUN PERADABAN MODERN - Mastori, Mastori (Jurnal Al-Hikmah: Jurnal Dakwah, 2024)
Abstract, Normatively, the Qur'an labels Muslims as the best people compared to other people. However, in fact, the condition of Muslims today is experiencing a downturn in various aspects of life. The reality of the gap that exists between Islam and its followers is the driving factor for conducting this research. To obtain in-depth results, the method used in this research is a qualitative method which is based on library data, in the form of books, journals and other library sources related to the research object. After the data is collected it is then analyzed descriptively to understand phenomena in depth and contextually. This research found several important findings: first, the Prophet Muhammad was the founding father of Islamic civilization so that Muslims throughout their long history have had a very strategic role in making contributions to world civilization. Second, during its development, Islamic civilization gradually experienced decline. This happened when Muslims began to be separated from their teaching system. Third, da'wah to raise Muslims from their downturn must be done as the Prophet Muhammad built Islam as the foundation of civilization.